Intellectual Property Related Generic Defense Strategies in the European Pharmaceutical Market Implications of the EU Commission's Sector Inquiry from an IP, Competition Law and Economic Perspective - Philipp, Marc P. (Munich Intellectual Property Law Center - MIPLC, 2011)
This book discusses the implications of the 2009 EU Commission's Pharmaceutical Sector Inquiry on originator's opportunities to apply Intellectual Property related measures in defending against generic competition. It argues that on the one hand recent developments in EU competition law do indeed impose potential limitations on an originator's ability to block or delay generic market entry. On the other hand, the book calls for a differentiated assessment of the rather broad allegations made by the sector inquiry. The book thereby presents and thoroughly analyzes six key issues identified by the EU Commission in the inquiry's final report: Blocking/defensive patenting, patent thickets, patent-related disputes and litigation, follow-on innovation, authorized generic entries and patent settlement agreements as well as interventions into generic marketing authorization. The analysis aims at reducing legal uncertainty by providing a clearer picture of legal boundaries between legitimate and problematic conduct under Arts. 101 and 102 TFEU. The book also puts the sector inquiry's findings into a forward-looking perspective by highlighting industry trends with the potential to transform traditional originator and generic business models. The author studied economics and law, has gained substantial expertise about strategy development as a consultant to the pharmaceutical industry and currently leads strategic research management at a large life sciences public research organization in Germany.